Epidemiological and Genetic Characteristics of Porcine Reproductive and Respiratory Syndrome Virus in South China Between 2017 and 2021 - Fang, Kui; Liu, Shudan; Li, Xiangmin; Chen, Huanchun; Qian, Ping (Frontiers in Veterinary Science, 2022)
Porcine reproductive and respiratory syndrome virus (PRRSV) remains a major threat to the swine industry in China and has caused enormous loss every year. To monitor the epidemiological and genetic characteristics of PRRSV in South China, 6795 clinical samples from diseased pigs were collected between 2017 and 2021, and 1279 (18.82%) of them were positive for PRRSV by RT-PCR detecting the ORF5 gene. Phylogenetic analysis based on 479 ORF5 sequences revealed that a large proportion of them was highly-pathogenic PRRSV (409, 85.39%) and PRRSV NADC30-like strains (66, 13.78%). Furthermore, 93.15% of these highly-pathogenic strains were found to be MLV-derived. We next recovered 11 PRRSV isolates from the positive samples and generated the whole genome sequences of them. Bioinformatic analysis showed that seven isolates were MLV-derived. Besides, six isolates were found to be recombinant strains. These eleven isolates contained different types of amino acid mutations in their GP5 and Nsp2 proteins compared to those of the PRRSVs with genome sequences publicly available in GenBank. Taken together, our findings contribute to understanding the prevalent status of PRRSV in South China and provide useful information for PRRS control especially the use of PRRSV MLV vaccines.